Please touch (Revista Espaço Acadêmico, 2011)
Abstract: This article discusses how, in Brazilian society, people tend to touch one another more freely in public than in other societies. Using several anecdotes, the article explores the ways in which men greet each other, women reach out to hug and kiss each other, how children relate to their mothers, and how even within the same society habits and mores related to physical touch change in time.